Sams teach yourself Windows XP - Perry, Greg M. (Sams teach yourself all in one., 2005)
If you're new to the world of Windows XP and are daunted by the thought of having to figure it all out on your own, Sams Teach Yourself Windows XP All in One can help. This all-inclusive reference book will teach you how to not only use your Windows XP system, but also how to utilize digital media and Internet features. Learn how to set up a home network, as well as how to upgrade, repair and protect your PC from viruses, spam and spyware. Updated to include information relating to the Windows XP Server Pack 2, Sams Teach Yourself Windows XP All in One will help you get the most you can out of your Windows XP-based computer.